IMPLEMENTASI PENDIDIKAN POLITIK DALAM PENCEGAHAN TINDAK PIDANA KORUPSI - Muhammad David; Yoga Bestari; Panggih Nur Adi (CIVITAS (JURNAL PEMBELAJARAN DAN ILMU CIVIC), 2020)
Abstrak — The research entitled "The Application of Political Education in Preventing Corruption Crime” is a study that uses a qualitative approach and a case study method. The purpose of this study is to describe how the application of Political Education in preventing criminal acts of corruption; Strategy in preventing corruption that involves party cadres. The reason for carrying out this research is to identify how the strategy of implementing party political education in preventing corruption, especially in DPW PKS Jawa Barat. The determination of research informants was carried out by a purposive sampling technique. Data collection research was conducted by interview, observation and documentation techniques. Data analysis techniques in this study used data reduction techniques, data presentation, drawing conclusions and verification. The validity of the data used is the source and technique triangulation. The results showed that the application of political education in DPW PKS Jawa Barat in an effort to prevent corruption was based on the development of Islamic political morals carried out in a curricular, routine and continuous manner. Political education is carried out through persuasive, detective and repressive designs. Keyword: Political, Education, Corruption